2021
DOI: 10.1002/ceas.12223
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the reality of empathy

Abstract: This pretest/posttest experimental design study investigated the use of virtual reality to teach school counseling students empathy, as measured by the Empathy Quotient. An independent samples and paired‐samples t‐test were used to analyze students’ scores in the experimental and control groups. The study's results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…7.1 Prosocial Efects 7.1.1 Empathy for Virtual Agents. Recent studies have investigated the use of games, and at a more broader level, virtual experiences, as mediums for generating empathy [28,41,44,58]. Arguments have been made for the impact of virtual perspective-taking to create similar empathetic outcomes within real life [41,42,77], for example, Paiva et al showed that emphatic virtual agents can aford users the capacity to respond empathetically as if they were in the same situation [93].…”
Section: Discussionmentioning
confidence: 99%
“…7.1 Prosocial Efects 7.1.1 Empathy for Virtual Agents. Recent studies have investigated the use of games, and at a more broader level, virtual experiences, as mediums for generating empathy [28,41,44,58]. Arguments have been made for the impact of virtual perspective-taking to create similar empathetic outcomes within real life [41,42,77], for example, Paiva et al showed that emphatic virtual agents can aford users the capacity to respond empathetically as if they were in the same situation [93].…”
Section: Discussionmentioning
confidence: 99%